2007
DOI: 10.1111/j.1365-2222.2007.02867.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral challenges are needed in the diagnosis of β‐lactam hypersensitivity

Abstract: In the diagnosis of beta-lactams allergy, if all skin tests are negative, skin tests with other determinants and provocation tests under strict surveillance are mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 27 publications
3
83
2
2
Order By: Relevance
“…Indications for skin tests are reported in Boxes 2 and 3. When positive, skin tests reduce the requirement for drug challenge [102,103]. Testing should be carried out shortly after the reaction has occurred because a long interval between the reaction and skin testing reduces the likelihood of a positive response [104].…”
Section: Skin Testingmentioning
confidence: 99%
“…Indications for skin tests are reported in Boxes 2 and 3. When positive, skin tests reduce the requirement for drug challenge [102,103]. Testing should be carried out shortly after the reaction has occurred because a long interval between the reaction and skin testing reduces the likelihood of a positive response [104].…”
Section: Skin Testingmentioning
confidence: 99%
“…In comparison, a study conducted by Bousquet PJ et al, which also followed the ENDA recommendations to test allergic reactions to β lactams, also included adults with a median age of 32 years. 19 A meta-analysis conducted by Harandian et al, has concluded that the prevalence of allergy to penicillin groups is more in adults (7.78%) when compared to children (1.98%). 22 It was also observed that all patients who were allergic to β lactam antibiotics were less than 56 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have utilized the skin prick test in different dilutions in order to identify immediate reactions to β lactam antibiotics. 19,25 A study by Sullivan et al has utilized skin tests in the detection of penicillin allergy only, wherein a total of 63% of patients tested positive and out of these, 57.2% were inpatients. 21 Another study by K. Lammintausta et al, assesses the usefulness of skin tests to prove drug hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations